Imaging in congenital inner ear malformations—An algorithmic approach - Bhagat, Abhinav C; Kumar, Jyoti; Garg, Anju; Prakash, Anjali; Meher, Ravi; Arya, Shivali (Indian Journal of Radiology and Imaging, 2020)
Malformations of the inner ear are an important cause of congenital deaf-mutism. Arrest in embryologic development of inner ear during various stages gives rise to the variety of malformations encountered. Current treatment options include hearing aids, cochlear implants, and auditory brainstem implants (ABI). With the advent of cochlear implant surgery and ABI, decent functional outcomes can be obtained provided such cases are diagnosed correctly and timely. To that end, high-resolution computed tomography (HRCT) has a fundamental role in the assessment of these conditions, ably supplemented by magnetic resonance imaging (MRI). The purpose of this pictorial essay is to illustrate the imaging features of inner ear anomalies in children with congenital deaf-mutism as per the latest terminology and classification and provide an algorithmic approach for their diagnosis.
Keywords: Cochlear implant; congenital deaf-mutism; high-resolution computed tomography; inner ear; Mondini; magnetic resonance imaging